'Baseline-offset' scheme for a methane remote sensor based on wavelength modulation spectroscopy. (27th June 2016) - Ding, Wuwen; Sun, Liqun; Yi, Luying; Zhang, Enyao
Abstract: A new scheme for methane remote sensing is presented. Unlike a standard published remote sensor based on wavelength modulation spectroscopy (WMS), a reference cell is inserted into the measuring optical path. This scheme inherits the merits of WMS and can achieve high signal-to-noise ratio especially in a low concentration environment. Experimental results show that the presented remote sensor can detect ambient methane with a detection limit of 5 ppm m (parts per million · meter) at a distance of 10 m and 16 ppm m for 20 m. A methane leak test shows the sensor can detect a methane leak of 15 ml min −1 within a range up to 37 m.